Intrauterine Growth Restriction Associated with Hematologic Abnormalities: Probable Manifestations of Placental Mesenchymal Dysplasia - Cristina Martinez-Payo; Rocio Alvarez Bernabeu; Isabel Salas Villar; Enrique Iglesias Goy (Thieme Medical Publishers, Inc., 2015)
Abstract Introduction Placental mesenchymal dysplasia is a rare vascular disease associated with intrauterine growth restriction, fetal demise as well as Beckwith-Wiedemann syndrome. Some neonates present hematologic abnormalities possibly related to consumptive coagulopathy and hemolytic anemia in the placental circulation. Case report We present a case of placental mesenchymal dysplasia in a fetus with intrauterine growth restriction and cerebellar hemorrhagic injury diagnosed in the 20th week of pregnancy. During 26th week, our patient had an intrauterine fetal demise in the context of gestational hypertension. We have detailed the ultrasound findings that made us suspect the presence of hematologic disorders during 20th week. Discussion We believe that the cerebellar hematoma could be the consequence of thrombocytopenia accompanied by anemia. If hemorrhagic damage during fetal life is found, above all associates with an anomalous placental appearance and with intrauterine growth restriction, PMD should be suspected along other etiologies.